Pulmonary toxicity in driver gene positive non-small cell lung cancer therapy. (3rd August 2022) - Zhao, Yi-Pu; Long, Yong
Abstract: Molecular targeted therapy significantly improved the therapeutic efficacy in non-small cell lung cancer (NSCLC) patients with driver gene mutations but also with new toxicity profiles. Although most patients treated with these drugs developed relatively controllable toxicity, significant pulmonary toxicity events, including interstitial lung disease, occurred in a small proportion of patients and can lead to discontinuation or even be life-threatening. Pulmonary toxicity associated with these anti-tumor drugs is a problem that cannot be ignored in clinical practice. The prompt diagnosis of drug-related lung injury and the consequent differential diagnosis with other forms of pulmonary disease are critical in the management of pulmonary toxicity. Current knowledge of the pathophysiology and management of pulmonary toxicity associated with these targeted drugs is limited, and participants should be able to identify and respond to the development of drug-induced pulmonary toxicity. This review offers information about the potential pathogenesis, risk factors and management for the development of these events based on the available literature. This review focused on pulmonary toxicities in driver gene-positive NSCLC therapy by describing the related adverse events to promote the awareness and management of this important toxicity related to antitumor-targeted therapy.